Yellow fever mosquito Aedes aegypti (Linnaeus) (Insecta: Diptera: Culicidae) - Catherine Zettel; Phillip Kaufman (EDIS)
EENY-434, an 8-page illustrated fact sheet by Catherine Zettel and Phillip Kaufman, is part of the Featured Creatures collection. It describes this container-inhabiting mosquito that is the primary vector of yellow fever — its synonymy, distribution, life cycle, medical importance, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.